PENINGKATAN KAPASITAS IBU DALAM PENCEGAHAN STUNTING DI NAGARI KOTO TANGAH BATU AMPA KECAMATAN AKABILURU KABUPATEN LIMA PULUH KOTA - Elidahanum Husni; Vionna Adhisti; Rinaldiansyah Rinaldiansyah (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Stunting is a condition characterized by inhibited physical growth and development in children due to inadequate nutrition. This is a serious issue that can have long-term impacts on the quality of a child's life and future. Preventing the risk of stunting during the first 1000 days of life is a crucial effort in maintaining the health and development of children from the early stages of their lives. To address stunting, a holistic approach is needed, particularly involving the role of mothers in prevention efforts. The objective of this activity is to enhance mothers' knowledge about stunting and its prevention in Nagari Koto Tangah Batu Ampa, Akabiluru District, Lima Puluh Kota Regency. The methods employed in the activity include counseling and question and answer sessions on stunting prevention and the importance of the first 1000 days of life, along with the distribution of informational pamphlets to participants at the integrated health post. The results of this activity reflect active participation by the attendees, indicating a high level of interest and engagement in the counseling and Q&A sessions. Moreover, there is a noticeable increase in the percentage of knowledge and awareness among participants regarding stunting prevention. Thus, this activity has a positive impact on enhancing the capacity of mothers as key agents in stunting prevention in Nagari Koto Tangah Batu Ampa. These efforts are undertaken with the hope of making a positive contribution, leading to a reduction in stunting rates in Nagari Koto Tangah Batu Ampa and an improvement in the quality of human resources in the future.